The challenges of single-short spinal anaesthesia for caesarean section in a morbidly obese patient: a case report (2005)
An unusual case of morbid obesity, severe hypertension and twin gestation at 36weeks in an unbooked multigravid patient was presented for cesarean section. She was referred from a private clinic to the obstetric emergency unit of the University College Hospital, Ibadan with history of hypertension in pregnancy. She was a known hypertensive for ten years and her blood pressure was poorly controlled due to non-compliance with medications and medical check-up. She had been having progressive visual loss over the ten year period and had lost three, previous pregnancies. Following comprehensive clinical and radiological evaluation, she had a carefully planned single-shot spinal anaesthesia for cesarean delivery of a set of twin which was performed on a double operation table. She remained stable throughout the procedure and post operative period.